Management of change, lean practice and organisational performance of private companies in Malaysia - Ahmad, Hartini; Ma’aji, Muhammad M.; Jalil, Johari (Academy for Global Business Advancement (AGBA), 2015)
Organizations can gain competitive advantage from lean production practices. Such practices enable the organization to get superior performance through reduction of wastes and other related costs (Ohno, 2008).Industries are nowadays facing a problem of broad production in their organizations thus resulting to lots of wastage. This has seen many companies experience problems of waste along the supply chain and the liability to make the right products for customer satisfaction.Procurement managers are bound to embrace the essence of adopting lean production which is a business initiative to reduce waste in manufacture production.To this extent therefore, this initiative leverage companies to achieve long term competitive advantages by putting in place the proper production systems and technologies particularly with regard to product quality, shortening product design time, the reducing of wastage improving end customer satisfaction and inventory management (Womack &Jones). Organizations must anticipate and respond to environmental changes to ensure competitiveness and, ultimately, survival. One of the basic assumptions underlying much of the strategic management literature is that successful firms change their strategies to attain a better fit with the environment (Audia et al.,2000).Change is to do something different or new. In today‘s uncertain economic climate, many organizations are forced to make changes in order to survive. They need to respond quickly to the global revolution while at a local and national level have to keep up with new technology and competition if they want to stay ahead of the game (Edmonds, 2011). Regardless of the size of a business, change is going to happen at some point, but as no two organizations are the same, there is never going to be a template to meet everyone‘s needs. In reality, change cannot be wholly managed; it will emerge naturally once a strategy for change exists.For the Government Linked Companies (GLCs), becoming lean is extremely important due the enormous size of the companies.Their organizational performance depends on how well they manage their resources.Efficiently managed GLCs, and well formulated and implemented strategies are critical for the success of business organizations (Singh & Ang, 1999).GLCs in Malaysia are mainly the major providers of utilities, postal services, airlines, airports, public transport, water and sewerage, banking and financial services, automotive, plantation, and construction industries.These companies hire an estimated 5 percent (about 400,000 employees) of the national workforce, and accounts for approximately 36 percent of the Malaysian Stock Exchange market capitalization and 54 percent of the Kuala Lumpur Composite Index (Abdullah, 2005). With regard to the performance, lean practices are deemed to be able to improve organizational performance in terms of efficiency as well as effectiveness (Chen & Tan, 2011).The purpose of this paper is to investigate the adoption level of management of change and lean practices among the GLCs in Malaysia and also examine the effect of management of change and lean practices to the performance of these GLCs.Although this relationship has been studied by previous researchers (Agus & Hajinoor, 2012), the current study specifically focuses on the GLCs as no such setting has been investigated before.